2002
DOI: 10.1046/j.1365-2648.2002.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions of discharge planning in acute health care: a case study in one British teaching hospital

Abstract: The findings have important implications for nurses, managers and educational establishments. It is essential that social and medical diagnoses run parallel and that accurate information is collated and communicated within the multidisciplinary team. Further research into the impact of time pressures on communication, interprofessional working and the discharge process is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 31 publications
5
103
0
5
Order By: Relevance
“…This seems to be a persistent problem. According to a number of earlier studies, nursing staff state that discharge planning sessions are complicated due to differences in perception and shortcomings in the flow of patient information between the professionals involved [6][7][8] . It can be seen that the nursing staff in our study underestimate their need to participate to make discharge planning really work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This seems to be a persistent problem. According to a number of earlier studies, nursing staff state that discharge planning sessions are complicated due to differences in perception and shortcomings in the flow of patient information between the professionals involved [6][7][8] . It can be seen that the nursing staff in our study underestimate their need to participate to make discharge planning really work.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing staff at Swedish hospitals state in some qualitative studies [6,7] also reported in a case study from the UK [8] that carefully completed discharge planning are complicated to run due to differences in perception and shortcomings in the flow of patient information between the professionals involved. It also seems to be unclear when nursing staff in primary healthcare assume full responsibility for the patient's further care after discharge [6] .…”
mentioning
confidence: 99%
“…Several authors recognize that discharge planning still remains problematic and many questions have been raised about its effectiveness (2)(3)17) . The inappropriate preparation of patients and relatives and the consequent lack of knowledge and information concerning several aspects contribution the use of classification instruments represent when planning patients' care needs at home.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the family should be involved in all planning steps so as to understand the patients' health status and needs. The valuation of the social aspects of patient care is considered of fundamental importance, as it is an integral part of the discharge process (17) . Through the findings in this study, it is important to consider the hospital discharge process, as well as the …”
Section: Discharge Guidance -Stepmentioning
confidence: 99%
“…Sometimes this information can be in a language that is foreign to ward nurses, such as terminology like metabolic alkalosis. Atwal (2002) proposes that if nurses do not comprehend the information they are given as part of handover then they do not question it, potentially allowing adverse events to occur during a patient's hospital admission. Whittaker and Ball (2000) outlined factors such as documentation, assessment, dependency, and workload as important information in order to provide appropriate ongoing nursing care for patients.…”
Section: Transfer From Intensive Care: the Ward Nurses' Experiencementioning
confidence: 99%